106 Diversity of clinical phenotype of patients with pyruvate dehydrogenase deficiency due to PDHA1 gene mutations. (11th October 2021) - Šikić, Katarina; Ramadža, Danijela Petković; Žigman, Tamara; Barišić, Nina; Lehman, Ivan; Mayr, Johannes A; Prokisch, Holger; Wortmann, Saskia B; Sperl, Wolfgang; Mesarić, Nikola; Rahelić, Valentina; Fumić, Ksenija; et al.
Abstract : Pyruvate dehydrogenase (PDH) is a mitochondrial multiunit complex which catalyzes pyruvate oxidation (derived mainly from glucose) to acetyl-CoA which then enters tricarboxylic acid cycle. Its deficiency results in accumulation of lactate and alanine. Lactate/pyruvate ratio is normal. Brain is almost always affected because it obtains energy primarily from oxidation of glucose. PDH deficiency is most commonly due to mutation in an X-linked pyruvate dehydrogenase E1 alpha subunit gene (PDHA1). Diagnosis is a challenge especially in females not only because of variable clinical phenotype but also because of skewed X-chromosome inactivation – its pattern varies among individuals, but also among different tissues of the same individual. Therefore, measuring PDH activity is not a reliable guide to the diagnosis in females. Gene analysis may be used to confirm the diagnosis. Causal treatment options include thiamine (cofactor of PDH), ketogenic diet and dichloroacetate. The goal of the study is to alert medical professionals to clinical variability of PDHC deficiency and thus make easier early diagnosis. We present a spectrum of clinical phenotypes of six patients with PDH deficiency diagnosed and treated in our Center. In patients 1 and 2 disease started antenatally – ultrasonography revealed brain ventriculomegaly. After birth MR demonstrated agenesis of corpus callosum, ventriculomegaly, cerebellar hypoplasia. Afterwards those patients had seizures and severe psychomotor retardation. Patient 3 had conatal hypotonia, respiratory difficulties and severe lactic acidosis. MRI revealed mild diffuse brain atrophy. At 8 years he has generalized hypotonia, walks with support. At age 6 months patient 4 presented with somnolence, metopic synostosis and mild white matter atrophy and ventriculomegaly. At 6 years she has hypotonia, moderate psychomotor retardation and ataxia. Patient 5 presented at 3 months with acute encephalopathy of unclear etiology. At 7 years she has isolated epilepsy and normal psychomotor development. Her older brother died at the age of 17 days due to cardiorespiratory failure of unknown cause. Patient 6 have had intermittent ataxia since 1 year and 8 months of age. Now at 10 years he has normal cognition. All patients had elevated plasma alanine and lactate (2, 66-19, 9 mmol/L; ref. range 0, 63-2, 40), and CSF lactate (3, 64-8, 52 mmol/L; ref. range 1, 2-2, 1), with normal lactate/pyruvate ratio. All patients were on ketogenic diet and thiamine treatment. No patient had regression or deterioration while on therapy. PDH deficiency should be in differential diagnosis of most neurological signs and symptoms. Early diagnosis may enable optimal treatment and proper genetic counseling.